The actualization of literacy skills in the Kampus Mengajar program - Annafs Azzakiyyah; Alief Noor Farida (ELT Forum: Journal of English Language Teaching, 2024)
As an integral part of engagement in today's global culture, where almost all aspects of life are shifting to digital formats, 21st-century literacy skills have become essential for participation in education. This special edition highlights the role of tertiary students' literacy skills in achieving the goals of the Kampus Mengajar (KM) program. The actualization of literacy skills must be designed to meet students' needs in improving their literacy skills as the main goal of the KM program. Different pedagogical strategies are needed to effectively address students' literacy skills competencies at the junior high school level. This research aimed to present the experiences of pre-service English as a Foreign Language (EFL) teachers in utilizing their literacy skills while participating in the KM program. Three pre-service EFL teachers were engaged to provide information regarding their experiences as teacher assistants in the program. Using a thematic analysis design, data was collected through levelization, narrative framework, and interviews. The data obtained was analyzed descriptively to understand the contribution of supporting literacy skills and team collaboration in creating effective and enjoyable learning. The research results show that adequate support for literacy skills and good teamwork can help teachers create a fun and effective learning environment, which ultimately improves students' literacy skills. This research provides important insights into how well-designed and collaborative actualization can improve educational outcomes at the junior high school level.